Risk Behaviors Among Young Men Who Have Sex With Men in Bangkok: A Qualitative Study to Understand and Contextualize High HIV Incidence - Chemnasiri, Tareerat (J Homosex, 2018)
The Bangkok Men Who Have Sex With Men (MSM) Cohort Study has shown high HIV incidence (8–12/100 person-years) among 18–21-year-old MSM. These data led to a further study using qualitative methods among young (18–24 years old) MSM in order to understand the factors driving the HIV epidemic among YMSM. We conducted eight focus group discussions and 10 key informant interviews among YMSM in Bangkok, Thailand. Sociodemographic and behavioral data were collected using a questionnaire. We audio-recorded, transcribed, and analyzed qualitative and questionnaire data using computer software. The categories relating to risk behavior were (1) the use of social networks for seeking sexual partners and the marketing promotions of MSM entertainment venues, (2) social influence by peers and older MSM, (3) easy access to high parties and group sex, (4) easy access to club drugs, (5) conceptions related to HIV risk, and (6) sexual preferences of YMSM. Increased HIV testing, same-sex education, and YMSM-specific HIV prevention efforts are urgently needed for YMSM in Bangkok.